The Teachers and Students’ Perception about Demotivating Factors on the Students’ Speaking Skill of 2nd grade of Senior High School in SMA Negeri 1 Seririt - ., Ida Ayu Kade Putri Pradnyani; ., Dra.Ni Made Ratminingsih, MA; ., Dra. Luh Putu Artini, MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Tujuan penelitian ini adalah mengidentifikasi faktor-faktor penyebab menurunnya motivasi pada keterampilan berbicara siswa kelas 2 di SMA Negeri 1 Seririt berdasarkan persepsi siswa dan guru. Penelitian ini adalah penelitian deskriptif. Metode penelitian ini adalah survei. Untuk mengumpulkan data, instrumen yang digunakan adalah kuesioner. Kuesioner tersebut disebar kepada siswa maupun guru. Hasil penelitian menunjukkan bahwa siswa mengidentifikasi tiga dari sembilan faktor yang direkomendasikan oleh Dornyei (2001) yang dikutip dari Jomairi (2011). Selain itu, siswa mengidentifikasi sembilan faktor tambahan berdasarkan persepsi mereka sendiri. Penelitian ini juga menunjukkan bahwa guru mengidentifikasi dua dari sembilan faktor yang direkomendasikan oleh Dornyei (2001) yang dikutip dari Jomairi (2011). Lebih lanjut, guru mengidentifikasi empat faktor tambahan berdasarkan pengalaman mengajar mereka di kelas. Kata Kunci : persepsi, faktor penyebab menurunnya motivasi, keterampilan berbicara. The purpose of the study was finding out the demotivating factors on the 2nd grade students’ speaking skill based on the students and teachers’ perception in SMA Negeri 1 Seririt. The study was a descriptive research. The method of the study was survey. In order to collect the data required, questionnaire was used as a means of collecting data both from the students and teachers. Therefore, the questionnaire was differentiated into student’ questionnaire and teacher’ questionnaire. As a result, the study showed that the students identified three out of nine factors suggested by Dornyei (2001) cited in Jomairi (2011) as demotivating factors on their speaking skill. In addition, the students conveyed nine additional demotivating factors based on their own perception. Besides that, the study showed that the teachers identified two out of nine factors suggested by Dornyei (2001) cited in Jomairi (2011) as demotivating factors on the students’ speaking skill. Furthermore, the teachers conveyed four additional demotivating factors based on their experiences in the classroom. keyword : perception, demotivating factors, speaking skill.